La Città Altra:Storia e immagine della diversità urbana: luoghi e paesaggi dei privilegi e del benessere, dell'isolamento, del disagio, della multiculturalità - Massimo Visone (FedOA - Federico II University Press, 2018)
This volume proposes a rich corpus of papers about the 'Other City', a subject only few times dealt with, but worthy of all our attention: it imposes itself on the scene of international modern and contemporary historiography for its undeniable topicality. Throughout history, the city has always had to deal with social 'otherness', i.e. with class privileges and, consequently, with discrimination and marginalization of minorities, of the less well-off, of foreigners, in short, with the differences in status, culture, religion. So that the urban fabric has ended up structuring itself also in function of those inequalities, as well as of the strategic places for the exercise of power, of the political, military or social control, of the spaces for imprisonment, for the sanitary isolation or for the 'temporary' remedy to the catastrophes. From the first portraits of cities, made and diffused at the beginning of the fifteenth century for political exaltation purposes or for religious propaganda and for devotional purposes, which often, through increasingly refined graphic techniques, distort or even deny the true urban image, we reach, at the dawn of contemporary history, the new meaning given by scientific topography and new methods of representation; these latter aimed at revealing the structure and the urban landscape in their objectivity, often unexpected for who had known the city through the filter of 'regime' iconography. The representation of the urban image still shows the contradictions of a community that sometimes includes and even exalts the diversities, other times rejects them, showing the unease of a difficult integration.